(untitled) (The Journal of Psychology and Sociology, 2025)
The creative class is a new factor in shaping the social, economic and cultural spheres of the city, influencing its attractiveness to talents and the comfort of living. The purpose of the study is to analyze the factors of institutionalization and development of the creative class in Almaty, the largest metropolis in Kazakhstan. The theoretical framework of this study is the theories of Richard Florida’s creative class and Charles Landry’s creative city. The main ideas of the study: the creative class in Kazakhstan is insufficiently institutionalized, the city of Almaty is an important center of innovation and creativity in Kazakhstan, which has the potential to institutionalize the creative class due to the concentration of the infrastructure of creative industries, therefore, the phenomenon of the creative class has positive consequences for Almaty as a creative center. The scientific significance lies in the fact that theoretical knowledge about the possibilities of developing the potential of Almaty as a center of attraction for creative talents has been expanded and supplemented. The practical significance lies in the fact that the in-depth expert information obtained will be used to develop recommendations on support measures for the further institutionalization of the creative class in Almaty. A qualitative method was used for this study – an expert interview. To analyze the expert interview, the methodology of grounded theory was applied, which is a set of inductive procedures aimed at climbing from unstructured data to their conceptualization. As a result, a paradigmatic model was constructed that demonstrates the logical relationship of the central categories identified during the analysis. The conducted research proves the applicability of the theories about the creative class of R. Florida and C. Landry in the Kazakh context, namely, the existence of a creative class in Almaty and the city of Almaty as a center of attraction for creators. Keywords: creative class, creative industries, creator, creative city, institutionalization.